ANALYSIS OF LEADERSHIP STYLE IN PENGADILAN NEGERI SITUBONDO - Septyawan, Dany Dhiman (Department of Management, 2014)
The purpose of this study is to describe the subordinate maturity, the leadership style of task behavior and relationship behavior and, Analyze the leadership style according to the theory of Hersey and Blanchard. Analyzer used in this research is by using scale analysis. it can be concluded that the level of maturity subordinate in Pengadilan Negeri Situbondo can be described that for the civil service in the category of high, common parts are very high and tge financial section included in the high criteria. Leadership style task behavior on the part of personel, general and financial sections include in the high criteria. Behavior on the part of employment relationship in the category of very high while for the public and included in the criteria of high finance. Leadership style according to the theory of Hersey and Blanchard in Pengadilan Negeri Situbondo is consultative.The suggestion in this research that the leadership should be more active in controlling the activities undertaken bye the employees to provide input and direction so that employees can carry out operational activities of the agency in accordance with the conditions set. Leaders must set a deadline for the finalization of the work so that the work can be completed on time so that the direction given is actually run in line with expectations and leadership should provide encouragement or motivation to employees in order to complete the work that is the responsibility in accordance with the provisions set.Keyword: Leaderhip Style, Behavior Relationship, Task Behavior, Hersey and Blankhard Theory.